STRATEGI BAWASLU KARAWANG DALAM MENINGKATKAN KESADARAN PEMILIH PEMULA GUNA PENCEGAHAN KAMPANYE HITAM: PERSPEKTIF SOSIALISASI POLITIK - Gultom, Puput Mega Lestari; Kurniansyah, Dadan (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2025)
This study aims to analyze Bawaslu Karawang's strategy in raising awareness of novice voters to prevent black campaign practices, using the perspective of Paul Allen Beck's political socialization theory. The research method used is qualitative with a descriptive approach where data is obtained through in-depth interviews with Bawaslu Karawang staff and document analysis related to the socialization program. The results showed that Bawaslu Karawang has conducted intensive socialization through an institutional structure that is evenly distributed to the village level, with material that focuses on the prohibition of black campaigns, hoaxes, and discrimination. However, the effectiveness of the program is still hampered by limited reach, frequency, and the dominant one-way delivery method. Although the cognitive understanding of novice voters has increased, the value of political participation in the Karawang elections has not shown a significant change, indicating that the expected character change has not been fully achieved. The conclusion of this study is that Bawaslu Karawang's strategy needs to be strengthened by innovating interactive methods, expanding outreach to remote areas, and increasing the involvement of novice voters in program design. These recommendations are expected to increase the effectiveness of political socialization in preventing black campaigns and building sustainable political awareness.